Association between serum biomarkers and oral health status in children with chronic kidney disease: A cross-sectional study - KAYA, REMZİYE; ALPAY, HARİKA; KARGÜL, BETÜL (My University, 2023)
Objectives: The aim of this study was to investigate the association between serum biomarkers and oral health parameters in children with chronic kidney disease (CKD). Materials and methods: Serum hemoglobin, blood urea nitrogen, serum creatinine, calcium, parathormone, magnesium, and phosphorus levels were measured in 62 children with CKD aged between 4 and 17 years. Intraoral examinations of the patients were performed by two different pediatric dentists. Dental caries was assessed using the decayed-missing-filled-teeth (DMFT/dmft) indexes, and oral hygiene was assessed using the debris (DI), calculus (CI), and simplified oral hygiene (OHI-S) indexes. Spearman’s rho coefficient and generalized linear modeling were used to examine the association between serum biomarkers and oral health parameters. Results: The results of the study showed that there were negative and statistically significant correlations between serum hemoglobin and creatinine levels and dmft scores in pediatric patients with CKD (p = 0.021 and p = 0.019, respectively). Furthermore, blood urea nitrogen levels and DI and OHI-S scores (p = 0.047 and p = 0.050, respectively); serum creatinine levels and DI, CI, and OHI-S scores (p = 0.005, p = 0.047, p = 0.043, respectively); and parathormone levels and CI and OHI-S scores (p = 0.001 and p = 0.017, respectively) were found to be positively and statistically significantly related. Conclusions: There are associations between various serum biomarker levels and dental caries and oral hygiene parameters in pediatric patients with CKD. Clinical relevance: The impact of changes in serum biomarkers on oral and dental health is important for dentists’ and medical professionals\" approaches to patients\" oral and systemic health.
Keywords: Tıp; Diş Hekimliği; Sağlık Bilimleri; Medicine; Dentistry; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; General Dentistry; Biomarkers; Chronic kidney disease; Dental calculus; Dental caries; Oral hygiene